DESIGN AND ASSESSMENT OF LOW-COST DUAL AXIS SOLAR TRACKING SYSTEMS FOR MAXIMUM SOLAR PHOTOVOLTAIC POWER EXTRACTION - Yusuf, Aliyu; Ali, M. H. (FUDMA Journal of Sciences, 2025)
A microcontroller-based dual axis solar tracking system is presented and implemented using computational algorithm. The experiment is conducted in two different test days; test day1 28th April 2020 and test day2 29th May 2020 for the evaluation of data collected in Zaria-Nigeria in a site located at 11.092 o N Latitude, 7.72o longitude. The panel is fixed at inclination of the site’s latitude with respect to the horizon on the northern hemisphere facing south. Whereas the automatic tracking mechanism is allowed to track the sun’s trajectory automatically in one axis (single axis) and two axes (dual axis). Radiation intensity sensors circuit is designed using Light Dependent Resistors (LDR) and Microcontroller on which the tracking algorithm was compiled. Iterative method based on Newton-Raphson is used to characterize the Photovoltaic (PV) panel. The study shows that the single axis generated 34.8% and 26.2% average increase in efficiency than that of the fixed mount for the test day 1 and test day 2 respectively. While the dual axis has 42.5% and 32.5% more than that of the fixed mount respectively for the test day 1 and test day 2. The daily average power calculated for dual axis produced more power than that of the single axis as well as that of the fixed mount system. The hardware chosen are of low-cost, versatile and simple to use. This automatic dual axis tracking topology can help to improve optimum power generation and management system.
Keywords: Dual Axis Solar Tracking System; Photovoltaic power optimization; Microcontroller-based solar tracker; Renewable energy efficiency